1981
DOI: 10.3109/00016358109162257
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Adhesiveness of Selected Dental Materials

Abstract: An investigation was conducted to determine the clinical adhesiveness of some commonly used dental materials. Contact angle measurement data, obtained under clinical conditions, were used to calculate the in vivo-critical surface tensions for enamel, gold, stainless steel, and a resin polymer. The results of this study showed that the adhesive properties of the artificial surfaces studied were considerably modified in the oral environment. Thus, after two hours these solids with diverse original surface chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 10 publications
5
33
0
3
Order By: Relevance
“…In this study, the materials were coated with saliva to form a pellicle. Jendresen and Glantz (18) have reported that dental materials, regardless of their original surface properties (high-or low-energy surface) assume the same surface properties as natural tooth surfaces covered with pellicle after only 1 to 2 h in the salivary environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the materials were coated with saliva to form a pellicle. Jendresen and Glantz (18) have reported that dental materials, regardless of their original surface properties (high-or low-energy surface) assume the same surface properties as natural tooth surfaces covered with pellicle after only 1 to 2 h in the salivary environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to begin to form within seconds (Skjørland et al 1995) of the exposure of clean enamel to saliva and to continue to develop over a period of hours (Busscher et al 1989) to form a layer a few hundreds of nanometres thick (measured in vivo on hydroxyapatite (Lie 1977)). The pellicle alters the surface properties of oral surfaces (Jendresen and Glantz 1981;de Jong et al 1982;Sipahi et al 2001) and may act as a boundary lubricant during occlusional contact between teeth (Hatton et al 1987). Boundary lubrication, distinct from hydrodynamic lubrication, is a mechanism that depends more on the chemical properties of a surface-bound film than the rheology of a confined lubricating fluid (Bowden and Tabor 1954;Bhushan 2002), and can be effective even when the separation between the rubbing surfaces is around the size of a molecule (Klein et al 1994;Briscoe et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…7,21,22 This might imply that after acid etching, the surface tension of enamel seems to play a major role in enhancing the mechanical interlocking between demineralized prisms and resin. Jendresen and Glantz 23 showed an increase of this superficial tension after enamel etching. Hence, the achievement of desirable shear strength does not depend on the requirement of adhesive resin wettability.…”
Section: Discussionmentioning
confidence: 99%